Assessment of nutrition and lifestyle of truck drivers - Mikulec, Anna; Zborowski, Marek; Cisoń-Apanasewicz, Urszula; Miczołek, Sonia; Plata, Artur; Mastalerz, Karolina (Journal of Education, Health and Sport, 2023)
Introduction Man’s lifestyle is of great importance for his health. Failure to comply with the rules of care for the physical and psychological sphere may be a risk factor for the development of lifestyle diseases. Drivers are a professional group that is particularly vulnerable to the influence of factors inconsistent with the principles of a healthy lifestyle, the most common of which are: improper habits and eating habits, the use of stimulants, insufficient physical activity, sedentary work, etc. Aim The aim of the study was to assess the diet and lifestyle of truck drivers. Material and methods The research tool was a questionnaire consisting of open-ended and choice questions concerning issues related to eating behaviors, regularity and frequency of eating meals, specific product groups, and health status. Based on the data provided by the drivers, the body mass index (BMI) was calculated. Results The respondents were dominated by men. Data analysis showed that some of them are overweight. Most of the respondents are characterized by proper eating habits related to the frequency and quality of the meals they eat. The most common ailments resulting from and related to the specificity of the work performed are back pain, nervousness, and sleep disorders. Conclusions There is a need to promote a healthy lifestyle among drivers, taking into account in particular the change and shaping of correct eating habits. The research can be the basis for further activities aimed at educating this professional group.